2022
DOI: 10.3390/brainsci12020125
|View full text |Cite
|
Sign up to set email alerts
|

Insular Involvement in Cases of Epilepsy Surgery Failure

Abstract: Background: Epilepsy surgery failure is not uncommon, with several explanations having been proposed. In this series, we detail cases of epilepsy surgery failure subsequently attributed to insular involvement. Methods: We retrospectively identified patients investigated at the epilepsy monitoring units of two Canadian tertiary care centers (2004–2020). Included patients were adults who had undergone epilepsy surgeries with recurrence of seizures post-operatively and who were subsequently determined to have an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…62% [ 1 , 2 , 35 , 37 , 38 ]. Each surgery is also a very invasive and risky procedure [ 1 , 2 , 8 , 37 , 38 , 39 , 40 ].…”
Section: Study Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…62% [ 1 , 2 , 35 , 37 , 38 ]. Each surgery is also a very invasive and risky procedure [ 1 , 2 , 8 , 37 , 38 , 39 , 40 ].…”
Section: Study Backgroundmentioning
confidence: 99%
“…Additionally. around 40% of epilepsy-affected patients suffer its drug-resistant version, which significantly limits potential treatment methods [ 1 , 2 , 3 , 5 , 8 ]. It affects the life quality of people affected with it in a significant way, as the seizures occur unexpectedly and can cause various physical injuries or even death [ 6 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Some studies have revealed that insular involvement in mesiotemporal lobe epilepsies could explain some persistent seizures after anterior temporal lobectomy (ATL). [5,6] In these patients, insular involvement is considered a potential risk factor for surgical failures. [6][7][8] The insula and temporal lobe (TL) belong to the limbic system and have very close fiber connections.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] In these patients, insular involvement is considered a potential risk factor for surgical failures. [6][7][8] The insula and temporal lobe (TL) belong to the limbic system and have very close fiber connections. The symptoms evoked by insular cortex stimulation are similar to those observed during TL seizures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation